AGAMA DALAM REPRESENTASI IDEOLOGI MEDIA MASSA - Muttaqin, Ahmad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
emphasize on business aspects. The messages brought by the media often functions more asan instrument for mobilizing readers than as a transformation of information. This is becausethe reader becomes an important part of business strategy, especially the claims of consumersin order to increase the bargaining power of actors industrialized economy.This paper describes how the media represent themselves in public life through thenews published. At this time, mass media has been transforming their political and socialinstitutions as the era of the old order and new order into the business institution. As abusiness institution, the main media orientation is capital gains. The media business is in theform of news information to the public discourse. In order to have large social effects of thediscourse, mass media are built on the principle of popularity and sensitivity. Religion invarious dimensions have two principles that are very attractive for the news object. Religionin the media is a representation that there are two possibilities, that is appropriate or notappropriate.The discussion in this paper starts from a view of the existence of the mass media,especially related to the question of whether the news is neutral or impartial. Ideologybecomes the entry point to analyze how mass media are produced and reproduced. In the end,the note describes how religion is represented by a media that has been filled with differentideologies.